Birthright: the book of man eaudiobook The book of man. - Resnick, Mike (Birthright, 2012)
An epic novel of human expansion across the stars This brilliant science fiction novel constructs a blueprint of mankind's history—social, political, economic, scientific, and religious—for the next eighteen thousand years. Through a series of adventures, it illustrates clear, focused ideas about our birthright and our destiny. Since this 1982 debut, Mike Resnick has emerged as one of the most honored science fiction authors of his time, picking up forty-odd Hugo and Nebula nominations and awards. He has set twenty-five novels and a novella in the future that was outlined in this book. Now, those who missed it the first time around can catch up on this mind-boggling, all-encompassing precedent to Resnick's fiction.